Damage localization and identification in WGF/epoxy composite laminates by using Lamb waves: Experiment and simulation. (1st April 2017) - Yang, Bin; Xuan, Fu-Zhen; Chen, Shaojie; Zhou, Shaoping; Gao, Yang; Xiao, Biao
Abstract: Lamb wave propagating behavior in woven glass fiber reinforced epoxy (WGF/epoxy) composite laminates was studied by simulation and experiment. A 3D finite element (FE) model was built in Abaqus/Explicit software with the help of user material subroutine to capture the wave propagating features in WGF/epoxy composite plate. The Lamb wave tests were carried out by a non-circular array with 8 piezoelectric (PZT) wafers. A defect imaging algorithm was developed using MATLAB based on the ellipse theory in time-dependent domains. Two defect imaging cases were carried out in the WGF/epoxy composite plate to verify the feasibility of the proposed algorithm. A good agreement between the simulated waveforms and experimental data was achieved. This indicates a great potential of the proposed algorithm in the field of damage localization and identification for WGF/epoxy thin-walled laminates.